Local community’s leader: role and authority of sub-district and village headman in the changing structure and context in Chiang Mai, Thailand - Ek-Iem, B. (International Journal of Agricultural Technology, 2021)
The results showed that the sub-district and village headman had the role and authority in a community, including governing and maintaining order, development and career promotion, conservation of natural resources and environment, justice, and service, at a highlevel ( = 4.07). The result from a multiple regression model also showed there were two variables that significantly positive influenced on role and authority of sub-district and village headman, including education and leadership (p< .05). Although the structure of local communities is changed by modernization and decentralization of the local government organization, the research finding found that the roles and authorities of the sub-district and village headman are still highly important to the local community